There is no happiness in positive affect: the pervasive misunderstanding of the rotated circumplex model - LaRowe, Lisa R.; Connell Bohlen, Lauren; Williams, David M. (Frontiers in Psychology, 2024)
Research on positive affect (PA) and negative affect (NA) is often guided by the rotational variant of the circumplex model of affect (RCMA; Watson, D., & Tellegen, A. (1985). Toward a consensual structure of mood. Psychological Bulletin, 98(2), 219-235.). According to the RCMA, PA and NA are posited to be orthogonal, with PA ranging from the union of positive valence and high activation (e.g., excited) to the union of negative valence and low activation (e.g., sluggish), and NA ranging from the union of negative valence and high activation (e.g., distressed) to the union of positive valence and low activation (e.g., relaxed). However, many authors incorrectly interpret the RCMA as positing that positively valenced affect (i.e., pleasure) and negatively valenced affect (i.e., displeasure)—rather than PA and NA, as defined in the RCMA—are orthogonal. This “received view” of the RCMA has led to significant confusion in the literature. The present paper articulates the “received view” of the RCMA and characterizes its prevalence in psychological research. A random sample of 140 empirical research articles on affect published in 14 high-impact journals covering a range of psychological subdisciplines were reviewed. Over half of the articles subscribing to the RCMA showed evidence of the “received view”, demonstrating that misuse of the terms PA and NA in the context of the RCMA is rampant in the psychological literature. To reduce continued confusion in the literature, we recommend abandoning use of the terms positive affect and negative affect. We further recommend referring to the two dimensions of the RCMA as positive activation and negative activation, and the two poles of the valence dimension as positive valence and negative valence (or pleasure and displeasure).